2023
DOI: 10.1093/ofid/ofad392
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Peer-Led Intervention to Increase COVID-19 Vaccine Uptake Among People Who Inject Drugs in San Diego County: Results From a Pilot Randomized Controlled Trial

Abstract: Background We evaluated the impact of a brief, peer-led intervention on COVID-19 vaccination among people who inject drugs (PWID) presenting at syringe services program (SSP) locations in San Diego County, California. Methods Between March and July 2022, PWID aged ≥18 years old without recent voluntary COVID-19 testing who were not up to date on COVID-19 vaccinations received a single-session motivational interviewing interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Participants with HIV had a higher prevalence of anti-S antibodies after adjustment for demographic factors, consistent with prior research demonstrating positive associations between HIV serostatus and COVID-19 vaccine uptake in this cohort and other samples of PWID ( Cepeda et al., 2022 ; Iversen et al., 2022 ; Strathdee et al., 2023a ). Participants with HIV in the current study sample were highly engaged in HIV care (e.g., 97% reported antiretroviral therapy use), which may have facilitated more encouragement and/or opportunity to receive the vaccine.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Participants with HIV had a higher prevalence of anti-S antibodies after adjustment for demographic factors, consistent with prior research demonstrating positive associations between HIV serostatus and COVID-19 vaccine uptake in this cohort and other samples of PWID ( Cepeda et al., 2022 ; Iversen et al., 2022 ; Strathdee et al., 2023a ). Participants with HIV in the current study sample were highly engaged in HIV care (e.g., 97% reported antiretroviral therapy use), which may have facilitated more encouragement and/or opportunity to receive the vaccine.…”
Section: Discussionsupporting
confidence: 88%
“…The finding that anti-S antibody prevalence was significantly lower among younger participants and marginally lower in female participants is consistent with our prior work in this cohort that found younger and female participants were less likely to be vaccinated against COVID-19 during March to June 2021 ( Cepeda et al., 2022 ). The association of age and sex with the probability of COVID-19 vaccine uptake has varied in other samples of PWID ( Des Jarlais et al., 2023 ; Harvey-Vera et al., 2022 ; Iversen et al., 2022 ; Strathdee et al., 2023a ). Notably, in our cohort, we also previously found that younger and female participants were also more likely to express high levels of COVID-19 vaccine hesitancy ( Cepeda et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the onset of the pandemic, a variety of approaches have been employed to improve COVID-19 vaccination rates among racial/ethnic minorities and vulnerable populations, including provider delivered educational interventions ( 22 ); patient education, incentives, reminders (e.g., text messaging), motivational interviewing ( 23 ); digital interventions ( 24 ); community-based approaches ( 25 , 26 ) and provision of vaccines in settings serving high risk populations ( 27 ). However, these studies have yield mixed findings, noting that some interventions had no notable change in COVID-19 vaccine uptake ( 23 ).…”
Section: Introductionmentioning
confidence: 99%